[Contribution of databases to regional and supra-regional quality improvement in rheumatologic treatment and patient management. Professional Society of Regional Cooperative Rheumatic Disease Centers] - Zink, A. (Z Rheumatol, 1998)
The uniform database of the German Collaborative Arthritis Centers is an important instrument for health services research, the observation of outcomes of daily rheumatological care, and for quality assessment in rheumatology. Deficits concerning modern medical and comprehensive therapy in non-specialized outpatient care were shown. The data give evidence of the benefits of the initiation of rheumatological care. Data of practice variation in rheumatology are used for internal quality assessment.